Syd Barrett : a very irregular head - Chapman, Rob; Barrett, Syd (London : Faber and Faber, 2010)
Biografie van Syd Barrett, stichtend lid van de psychedelische band Pink Floyd.
Includes bibliographical references (p. 413-415) and index.
Keywords: Barrett, Syd; Pink Floyd (Musical group).; Lyricists -- Great Britain -- Biography; Rock music fans -- Great Britain -- Biography; Rock musicians -- Great Britain -- Biography